Safe and Effective Anticoagulation with Warfarin within One-year Time Period- Team Work of Healthcare Professionals - Dhande, Priti; Kawade, Sushila; Chaudhari, Akshay (Indian Journal of Pharmaceutical Education and Research, 2024)
Background At the study site, Quality team found many incident reports of bleeding due to increased INR in patients on Warfarin anticoagulation therapy. These patients were unaware about adverse effects of anticoagulation therapy and drug-drug/food-drug interactions. Hence to ensure safety in anticoagulation with Warfarin, team of a Pharmacologist, Clinical Pharmacist and Quality manager decided to conduct a clinical audit to improve high alert medication safety with warfarin. Materials and Methods After obtaining Institutional Ethics committee approval, clinical audit proposal form was submitted to the Clinical Audit Committee. Clinical Pharmacists took their clinical rounds to identify patients on anticoagulation with warfarin, asked for their consent in local language, reviewed their case files for data and interviewed them. Action plan was made based on the observations in gap analysis conducted from April-May 2018. Interventions were planned to improvise these standards and analysis continued monthly. Bilingual warfarin education leaflets were given to all patients on warfarin therapy. Results Improved awareness on drug-drug and food-drug interactions was observed among the patients from 61.50% to 92.30% in one year. Increase in adherence of INR checking from 76.9% to 100% patients. ADRs to warfarin were recognized and action was taken to treat them within 24 hr by the end of one year of the study. Conclusion Marked improvement was observed in the patients’ awareness on drug-drug and food-drug interactions as well as INR monitoring, ADR reporting by clinicians and clinical interventions to prevent harm to the patient.
Keywords: Clinical Pharmacists; Audit; Warfarin; Interventions